2020
DOI: 10.4269/ajtmh.20-0483
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hospitalization and Mortality due to COVID-19 in Espírito Santo State, Brazil

Abstract: Brazil is, at the time of writing, the global epicenter of COVID-19, but information on risk factors for hospitalization and mortality in the country is still limited. Demographic and clinical data of COVID-19 patients until June 11th, 2020 were retrieved from the State Health Secretariat of Espírito Santo, Brazil. Potential risk factors for COVID-19 hospitalization and death were analyzed by univariate and multivariable logistic regression models. A total of 10,713 COVID-19 patients were included in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
104
10
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(158 citation statements)
references
References 47 publications
17
104
10
9
Order By: Relevance
“…Comparing our results evaluated in the state of Bahia, Brazil, with the reported results of other regions of the world, we see that, in an other state of Brazil, namely Espírito Santo, Soares et al [19] reported a higher mortality rate of 39.6% of the hospitalized patients, when compared to the mortality rate reported in this study (26.8%). Moreover, similar to our results, older age, shortness of breath and the kidney disease were also estimated to be risk factors associated with the mortality from COVID-19.…”
Section: Plos Onesupporting
confidence: 68%
See 2 more Smart Citations
“…Comparing our results evaluated in the state of Bahia, Brazil, with the reported results of other regions of the world, we see that, in an other state of Brazil, namely Espírito Santo, Soares et al [19] reported a higher mortality rate of 39.6% of the hospitalized patients, when compared to the mortality rate reported in this study (26.8%). Moreover, similar to our results, older age, shortness of breath and the kidney disease were also estimated to be risk factors associated with the mortality from COVID-19.…”
Section: Plos Onesupporting
confidence: 68%
“…The SARS-CoV-2 that causes the coronavirus disease 2019 (COVID- 19) arises from the RNA mutation of a virus isolated for the first time in 1937 and which initially expanded asymptomatically and with mild symptoms. However, SARS-CoV-2 is currently the pathogen that causes the most concern to the community around the world due to its high transmissibility, thus generating major impacts for health systems [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective case series using a Mexican nation-level dataset, current smokers were 23% less likely to be diagnosed with COVID-19 compared to non-smokers, and current smoking was not associated with adverse outcomes ( Giannouchos et al, 2020 ). In contrast, in a large sample of Brazilians patients, smoking was associated with the risk of hospitalization and adverse outcomes ( Soares et al, 2020 ). Smoking history may provide valuable information in identifying at-risk populations.…”
Section: Results and Observationsmentioning
confidence: 99%
“…In the group of COVID-19 mortality, the average prevalence of cardio-cerebrovascular disease was 15.15%. Seventeen studies ( Buckner et al, 2020 ; Cao et al, 2020 ; Guan et al, 2020 ; Huang et al, 2020 ; Khamis et al, 2020 ; Y. Li et al, 2020 ; Mao et al, 2020 ; Mendy et al, 2020 ; Petrilli et al, 2020 ; Romero-Sanchez et al, 2020 ; Wang et al, 2020 ; Wei et al, 2020 ; Xie et al, 2020 ; Xu et al, 2020 ; S. Yan et al, 2020 ; G. Zhang et al, 2020 ; J. J. Zhang et al, 2020 ) reported the disease severity of COVID-19 patients with cardio-cerebrovascular disease, and 14 studies ( T. Chen et al, 2020 ; Du et al, 2020 ; Halvatsiotis et al, 2020 ; Inciardi et al, 2020 ; Mehra et al, 2020 ; Nikpouraghdam et al, 2020 ; Ruan et al, 2020 ; Soares et al, 2020 ; Sousa et al, 2020 ; Tu et al, 2020 ; Wu et al, 2020 ; Y. Yan et al, 2020 ; Yuan et al, 2020 ; Zhou et al, 2020 ) reported the mortality of COVID-19 patients with cardio-cerebrovascular disease.…”
Section: Resultsmentioning
confidence: 99%